2018
DOI: 10.1183/13993003.01033-2018
|View full text |Cite
|
Sign up to set email alerts
|

ERS technical standard on bronchial challenge testing: pathophysiology and methodology of indirect airway challenge testing

Abstract: Recently, this international task force reported the general considerations for bronchial challenge testing and the performance of the methacholine challenge test, a “direct” airway challenge test. Here, the task force provides an updated description of the pathophysiology and the methods to conduct indirect challenge tests. Because indirect challenge tests trigger airway narrowing through the activation of endogenous pathways that are involved in asthma, indirect challenge tests tend to be specific for asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
155
0
13

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(170 citation statements)
references
References 181 publications
(225 reference statements)
2
155
0
13
Order By: Relevance
“…The expression of these mast cell genes was also assessed by copy number analysis of RNA isolated from epithelial brushings obtained at the time of research bronchoscopy. We found that the T2GM in induced sputum was associated with the number of copies of TPSAB1 (r 2 Figure 3F). In accordance with our results showing a relationship between the T2GM and the severity of indirect AHR, we found that the severity of EIB measured by the AUC30 was also associated with TPSAB1 (r 2 = 0.22, P = 0.006; Supplemental Figure 3D) and CPA3 (r 2 = 0.31, P = 0.0007; Supplemental Figure 3E) in induced sputum cells and not with CMA1 (r 2 = 0.00, P = 0.82; Supplemental Figure 3F).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The expression of these mast cell genes was also assessed by copy number analysis of RNA isolated from epithelial brushings obtained at the time of research bronchoscopy. We found that the T2GM in induced sputum was associated with the number of copies of TPSAB1 (r 2 Figure 3F). In accordance with our results showing a relationship between the T2GM and the severity of indirect AHR, we found that the severity of EIB measured by the AUC30 was also associated with TPSAB1 (r 2 = 0.22, P = 0.006; Supplemental Figure 3D) and CPA3 (r 2 = 0.31, P = 0.0007; Supplemental Figure 3E) in induced sputum cells and not with CMA1 (r 2 = 0.00, P = 0.82; Supplemental Figure 3F).…”
Section: Resultsmentioning
confidence: 85%
“…Asthma is a heterogeneous disorder with features of airway inflammation, reversible airflow obstruction, and airway hyperresponsiveness (AHR). Indirect AHR is a particularly important pathophysiologic finding because it is a highly specific feature of asthma not seen in other diseases (1,2), and because it is associated with the persistence of asthma (3). In contrast to direct AHR, in which an exogenous stimulus for bronchoconstriction is administered, indirect AHR is the result of the endogenous release of mediators from the airways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is one of the most prevalent chronic diseases in children worldwide . Exercise‐induced bronchoconstriction (EIB) is a common feature in asthma, but its mechanisms are not fully understood . There are two major hypotheses explaining the link between exercise and bronchial smooth muscle contraction, the thermal and the osmotic hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…feature in asthma, but its mechanisms are not fully understood. 2 There are two major hypotheses explaining the link between exercise and bronchial smooth muscle contraction, the thermal and the osmotic hypotheses. Exercise can cause cooling of the airways due to elevated ventilation, which is followed by rewarming at rest.…”
mentioning
confidence: 99%